Bending performance of nail-laminated bamboo-timber panels made with glubam and fast-grown plantation Chinese fir. (27th June 2023) - Li, T.Y.; Deng, J.Y.; Chen, J.Q.; Xiao, Y.; Shan, B.; Xu, H.; Qin, S.J.; Yu, Q.
Highlights: A novel structural nail-laminated panel constructed of engineered bamboo and local fast-grown Chinese fir was proposed in this study. Static bending tests were performed on twelve nail-laminated bamboo and timber (NLBT) specimens. This research provides a feasible and reasonable approach for developing local fast-grown species as structural components. Abstract: This study attempts to develop a novel structural nail-laminated panel constructed of engineered bamboo and local fast-grown plantation Chinese fir. An experimental program is reported in this paper on static bending behaviors of such nail-laminated bamboo-timber (NLBT) panel. Twelve NLBT specimens, including five short span specimens without butt joints and seven long span specimens with different butt joints were manufactured and tested. The panel span, species of sawn timber boards, the cross sectional configuration, and reinforcement measures of butt joints were chosen as the experimental parameters in the current investigation. The typical failure mode of the short span NLBT panels exhibited a multiple-fracture process caused by the tension failure of timber layers, while the overall collapse was much delayed or avoided attributed to the residual bending capacity provided by glubam layers. Test results demonstrate that the use of fast-grown Chinese fir instead of imported dimension lumber to combine glubam does not obviously reduce the bending performance of NLBT panels. The proposed vertical nailing reinforcement for butt joints can significantly improve the bending stiffness of the long span NLBT panels, and it is convenient for processing and assembling of NLBT components. Based on the ratio of bamboo and timber, a simple linear relationship is proposed for predicting the elastic modulus of the NLBT through regression analysis. The observed performance evaluation also reveals that the bending performance of the proposed NLBT structural panels is sufficient to meet the design requirements for using as the structural floors in offices and residential buildings. This research provides a feasible and reasonable approach for developing local fast-grown species as structural components.